Characterization of CD34+ hematopoietic cells in systemic mastocytosis: Potential role in disease dissemination. Issue 6 (13th February 2018) - Mayado, A.; Teodosio, C.; Dasilva‐Freire, N.; Jara‐Acevedo, M.; Garcia‐Montero, A. C.; Álvarez‐Twose, I.; Sánchez‐Muñoz, L.; Matito, A.; Caldas, C.; Muñoz‐González, J. I.; Henriques, A.; Sánchez‐Gallego, J. I.; et al.
Abstract: Background: Recent studies show that most systemic mastocytosis (SM) patients, including indolent SM (ISM) with (ISMs+) and without skin lesions (ISMs−), carry the KIT D816V mutation in PB leukocytes. We investigated the potential association between the degree of involvement of BM hematopoiesis by the KIT D816V mutation and the distribution of different maturation‐associated compartments of bone marrow (BM) and peripheral blood (PB) CD34 + hematopoietic precursors (HPC) in ISM and identified the specific PB cell compartments that carry this mutation. Methods: The distribution of different maturation‐associated subsets of BM and PB CD34 + HPC from 64 newly diagnosed ( KIT ‐mutated) ISM patients and 14 healthy controls was analyzed by flow cytometry. In 18 patients, distinct FACS‐purified PB cell compartments were also investigated for the KIT mutation. Results: ISM patients showed higher percentages of both BM and PB MC‐committed CD34 + HPC vs controls, particularly among ISM cases with MC‐restricted KIT mutation (ISMMC ); this was associated with progressive blockade of maturation of CD34 + HPC to the neutrophil lineage from ISMMC to multilineage KIT ‐mutated cases (ISMML ). Regarding the frequency of KIT ‐mutated cases and cell populations in PB, variable patterns were observed, the percentage of KIT ‐mutated PB CD34 + HPC, eosinophils, neutrophils, monocytes and T cells increasing from ISMs−MC and ISMs+MC to ISMML patients. Conclusion: The presence of the KIT D816V mutation in PB of ISM patients is associated with (early) involvement of circulating CD34 + HPC and multiple myeloid cell subpopulations, KIT ‐mutated PB CD34 + HPC potentially contributing to early dissemination of the disease.